Respon Pengunjung Terhadap Atraksi, Aksesibilitas, Amenitas, dan Pelayanan Tambahan Kambang Iwak Park Kota Palembang - Fauziawati Fauziawati; M. Syahirman Yusi; Fetty Maretha (Politeknik Negeri Sriwijaya, 2021)
This study aims to determine the response of visitors to Kambang Iwak Park as a tourist destination in the city of Palembang. The variables in this study are visitor responses related to components of tourist destinations with tourist attractions, accessibility, amenities, and ancillary services. This study used accidental sampling technique with a total sample of 130 respondents. This research shows that the component of tourist attraction is based on the calculation using the interpretation score that in the strongly agree category of 82%, this means that the statement is stated in accordance with the existing attractions in Kambang Iwak Park. The accessibility component is in the strongly agree category of 86%, this means that the statement is declared appropriate and perfect in the current state of accessibility in Kambang Iwak Park. The amenities component is in the strongly agree category of 84.7%, this means that visitors can still use the Iwak Park facilities and infrastructure that support activities on the object. The ancillary service component is in the very agree category of 81%, this means that the services provided can help visitors and provide visitor satisfaction.